Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/bcp.14141
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with biochemically detected and hospitalised acute kidney injury in patients prescribed renin angiotensin system inhibitors

Abstract: Aims: Therapy with angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB) is a mainstay of treatment for heart failure (HF), diabetes mellitus (DM) and chronic kidney disease (CKD). These agents have been associated with development of acute kidney injury (AKI) during intercurrent illness. Risk factors for AKI in patients prescribed ACEi/ARB therapy are not well described. Methods:We captured the incidence of AKI in patients commencing ACEi/ARB during 2009-2015 using anonymised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…ACE inhibitors reduce the production of angiotensin II, which results in vasodilation and reduced blood pressure. In this case, inhibiting the activities as an angiotensin-converting enzyme would relieve hypertension and hypertension-sensitive conditions, including heart failure, chronic kidney disease, or diabetes mellitus [45]. In mice, the role of the ACE/angiotensin II signaling has been investigated.…”
Section: Two Opposing Health Effects Of Ace On Admentioning
confidence: 99%
“…ACE inhibitors reduce the production of angiotensin II, which results in vasodilation and reduced blood pressure. In this case, inhibiting the activities as an angiotensin-converting enzyme would relieve hypertension and hypertension-sensitive conditions, including heart failure, chronic kidney disease, or diabetes mellitus [45]. In mice, the role of the ACE/angiotensin II signaling has been investigated.…”
Section: Two Opposing Health Effects Of Ace On Admentioning
confidence: 99%
“…We had previously shown that women tended to have lower doses of ACEIs prescribed relative to men, which may explain the reduced MACE benefit; however, this alone would not explain the greater AKI risk in women 29 . In clinical trials 30 and observational studies, 31 women were more likely to demonstrate an elevation in serum creatinine after initiating RAASIs, whereas the same findings were not replicated in other observational studies 13,32 . It is therefore unclear if women have a greater predisposition to renal injury while using RAASIs.…”
Section: Discussionmentioning
confidence: 96%
“…ACE inhibitors will reduce the production of angiotensin II, leading to vasodilation and reduced blood pressure. In this case, inhibiting the activities as an angiotensin-converting enzyme would relieve hypertension and hypertension sensitive health conditions, including heart failure, diabetes mellitus, or chronic kidney disease [37]. In mice, it also reduces AD symptoms in the mouse AD model [38].…”
Section: Two Opposing Health Effects Of Ace On Alzheimer's Disease (Ad)mentioning
confidence: 99%